Simulation of Hip Operations and Design of Custom-made Endoprostheses using Virtual Reality Techniques - Handels, H.; Ehrhardt, J.; Plötz, W.; Pöppl, S. J. (Methods of Information in Medicine, 2001)
In this paper a system for the virtual planning of hip operations with endoprosthetic reconstruction and its application in bone tumor surgery is described. The system enables the simulation of the operation and the construction of a custom-made implant depending on the chosen resection planes and the patient’s anatomy. During the planning process integrated virtual reality techniques facilitate the interaction with the three-dimensional (3D) medical objects. Stereo viewing improves the perception of the 3D nature of bone structures and tumors. In comparison to conventional planning procedures, different operation strategies and their influence on the geometry of the custom-made endoprosthesis can be easily compared. Furthermore, the combination of multi-modal image information (CT and MR) enables an accurate 3D visualization of the bone tumor within the bone.
Keywords: Virtual Reality; Surgical Planning; Multi-modality Imaging